A method of correction for the effect of optical traps in equilibrium microrheology experiments - ElSabry, ElHassan (AUC Knowledge Fountain, 2014)
Optically trapped dielectric particles experience a linear restoring force due to the trapping laser beam for small displacements of the trapped beads from the center of the optical trap. The optical force adds an apparent contribution to the measured shear elastic modulus of the solution in microrheology experiments. Traditional methods of correcting for the effect of the trap and obtaining the true shear elastic modulus of the solution involved taking measurements in separate purely viscous solutions using similar but not identical trapped beads under the same experimental conditions. A new method is proposed in this research to do this correction. It is based on finding the apparent response of the system including solution and trap at two different laser powers then extracting the true medium response from the measured responses. It was found to be an effective method to correct for the optical trap effect for samples of purely viscous solutions that theoretically should have zero elastic shear modulus. It was also tested in a solution of worm-like micelles to check its viability in solutions that have an inherent elastic component of shear modulus. Measurements in water yielded a zero elastic shear modulus and those in micelle solution agreed with previously published data for worm-like micelles solutions. The new method requires less labor and avoids possible sources of error involved in the traditional methods.